Institutional Distance, Regional Clusters and Performance of Foreign Subsidiaries: Evidences from Brazil - Jonas Fernando Petry; Mohamed Amal; Dinorá Eliete Floriani (BBR: Brazilian Business Review)
Institutional distance (ID) has come to be a key concept in understanding the determinant factors of the performance of a multinational company’s (MNC) subsidiaries in emerging economies. However, the results of empirical studies are contradictory and inconclusive. The objective of this study is to evaluate the effects of ID on the performance of foreign firms’ subsidiaries and the extent to which these effects may be mediated by locating these companies within regional clusters and by different choices of entry mode. Through a regression analysis of a sample of 308 subsidiaries of foreign firms, results show that whereas ID is negatively related with the firm’s performance, locations within clusters and access to the resources afforded by economies of agglomeration have positive effects on performance. Finally, the empirical evidence indicates that access to the resources of industrial clusters moderates the effects of ID on the performance, motivating MNCs to adopt overseas entry modes for complete control.